The Effects of Educational and Psychological Family-Based Early Intervention on the Motor Development of Children with Down Syndrome - Salar Faramarzi; Mokhtar Malekpour (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: The purpose of this study was to examine the effect of psychological and educational family- based early interventions on motor development of Isfahanian children with Down syndrome under age 5. Materials & Methods: In this experimental and interventional study, 36 parents who had children with Down syndrome were randomly selected and assigned into two groups by balanced randomized method. Hornby's counseling model and educational plan was implemented on experimental group. To collect data Winders motor developmental checklist and Gesell psycho-motor scale were used. Covariance statistical method was used to analysis the data. Results: Findings showed that there were significant differences in performance of children with Down syndrome, between experimental group and control group in both gross motor and psycho-motor skills (P<0.001). Conclusion: The results showed that psychological and educational family- based early interventions had significantly increased motor development in gross motor and psycho-motor skills of children with Down syndrome.